2016
DOI: 10.1590/0102-311x00063916
|View full text |Cite
|
Sign up to set email alerts
|

O lugar dos trabalhadores de saúde nas pesquisas sobre processos migratórios internacionais e saúde

Abstract: Resumo: Estudos sobre o processo saúde-doença-cuidados de imigrantes estabelecidos na cidade de São Paulo, Brasil, têm evidenciado uma complexa trama de relações nas demandas dos imigrantes e nas ações concebidas e planejadas pelos serviços de saúde. Nesse contexto, a intermediação dos trabalhadores da saúde na relação imigrantes-investigadores constitui importante forma de acesso dos últimos aos imigrantes sul-americanos, especialmente os bolivianos. Durante as investigações o acesso aos imigrantes ocorre den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
(24 reference statements)
0
5
0
4
Order By: Relevance
“…Over half of these studies [ 21 ] had been published in the previous five years (2014–2018), the rest between 2001 and 2013. More than half of them [ 22 ] used qualitative methods (ethnography, in-depth interviews, focus groups) and the rest were based on quantitative analysis of data collected in representative samples (community-level surveys or abortion care patients) or followed a mixed-methods approach (quantitative data from a survey of abortion care patients supplemented by in-depth interviews). All 79 studies met the minimum quality requirement set at 3 out of 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over half of these studies [ 21 ] had been published in the previous five years (2014–2018), the rest between 2001 and 2013. More than half of them [ 22 ] used qualitative methods (ethnography, in-depth interviews, focus groups) and the rest were based on quantitative analysis of data collected in representative samples (community-level surveys or abortion care patients) or followed a mixed-methods approach (quantitative data from a survey of abortion care patients supplemented by in-depth interviews). All 79 studies met the minimum quality requirement set at 3 out of 5.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil , several studies indicate that women rely on their network to locate where misoprostol can be procured. Who can be reached through these networks is very important, and can change the experience entirely: [ 22 ] members of feminist groups were mentioned as especially helpful in this regard, as well as illegal drug sellers, and women who had used misoprostol themselves [ 51 ]. “The speed and ease with which a woman triggers a wide network of care and facilities for an abortion is one of the signs of how the culture of abortion is shared among women in Brazil… [Women who had an abortion] assist other women to have an abortion” [ 52 ] (p. 1679, translated from Portuguese).…”
Section: Resultsmentioning
confidence: 99%
“…Over 350,000 Bolivian immigrants live in the city 17 and a recent seroprevalence study in this population found 4.4% with T. cruzi infection 18 . Bolivians primarily migrate to Sao Paulo in search of job opportunities and greater economic stability for their families [19][20][21] . Prior research on Bolivian immigrants living near downtown Sao Paulo indicated a predominantly young population working mainly in garment sweatshops; the majority earning between 1-3 times minimum wage 22 .…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, a correlação entre migração e saúde é complexa e permeada por fatores sociais como desigualdades socioeconômicas, preconceito, discriminação, iniquidades no acesso ao trabalho, moradia, educação e diferenças culturais entre os países. Nessa direção, concepções e práticas em saúde--doença-cuidado criados ou aprendidos no país de origem podem interferir nos "sistemas culturais de saúde" [2][3][4] do país receptor dos imigrantes. Cabe esclarecer para fins deste estudo que, como a doença é percebida a partir de um conjunto de experiências culturais do sujeito, os sistemas de saúde são também sistemas culturais 5 .…”
Section: Introductionunclassified